Metabolism and physiology of pathogenic bacterial obligate intracellular parasites - Mandel, Cameron G.; Sanchez, Savannah E.; Monahan, Colleen C.; Phuklia, Weerawat; Omsland, Anders (Frontiers in Cellular and Infection Microbiology, 2024)
Bacterial obligate intracellular parasites (BOIPs) represent an exclusive group of bacterial pathogens that all depend on invasion of a eukaryotic host cell to reproduce. BOIPs are characterized by extensive adaptation to their respective replication niches, regardless of whether they replicate within the host cell cytoplasm or within specialized replication vacuoles. Genome reduction is also a hallmark of BOIPs that likely reflects streamlining of metabolic processes to reduce the need for de novo biosynthesis of energetically costly metabolic intermediates. Despite shared characteristics in lifestyle, BOIPs show considerable diversity in nutrient requirements, metabolic capabilities, and general physiology. In this review, we compare metabolic and physiological processes of prominent pathogenic BOIPs with special emphasis on carbon, energy, and amino acid metabolism. Recent advances are discussed in the context of historical views and opportunities for discovery.